MATLAB Professional Applications in Power System - Saghafinia, Ali (IntechOpen, 2018)
Conventionally, the simulation of power engineering applications can be a challenge for both undergraduate and postgraduate students. For the easy implementation of several kinds of power structure and control structures of power engineering applications, simulators such as MATLAB/(Simulink and coding) are necessary, especially for students, to develop and test various circuits and controllers in all branches of the field of power engineering. This book presents three different applications of MATLAB in the power system domain. The book includes chapters that show how to simulate and work with MATLAB software for MATLAB professional applications of power systems. Moreover, this book presents techniques to simulate power matters easily using the related toolbox existing in MATLAB/Simulink.